Răspuns:
Explicație pas cu pas:
1 + 3 + 5 + ... + 2005 < x < 2+4+6+ .+ 2006
________
1 + 3 + 5 + ... + 2005 = 1003*(1 + 2005)/2 = 1003*2006/2 = 1003*1003 = 1006009
2005 = 1 + (n - 1)*2 = 1 + 2n - 2 = 2n - 1
2n = 2005 + 1 = 2006
n = 2006 : 2 = 1003 termeni in suma
________
2+4+6+ .+ 2006 = 1003*(2 + 2006)/2 = 1003*2008/2 = 1003*1004 = 1007012
2006 = 2 + (n - 1)*2 = 2 + 2n - 2 = 2n
n = 2006 : 2 = 1003
__________________
1006009 < x < 1007012
x = 1006010, 1006011, ..., 1007011 = 1002 numere naturale